Caregiver Life Satisfaction: Relationship to Youth Symptom Severity through Treatment - Athay, M. Michele (2012)
OBJECTIVE: This study utilized the Satisfaction with Life Scale (SWLS) to investigate the life satisfaction of caregivers for youth receiving mental health services (N = 383), specifically how it relates to youth symptom severity throughout treatment. METHOD: Hierarchical linear modeling (HLM) with a time-varying covariate was used to estimate the linear trajectory of caregiver life satisfaction and how it relates to youth symptom severity as rated by caregivers, youth, and clinicians. RESULTS: Initial caregiver life satisfaction was inversely related to caregiver and clinician rated youth symptom severity. Additionally, subsequent caregiver life satisfaction demonstrated a small but significant relationship to changes in youth symptom severity during treatment where a decrease in youth symptoms corresponded to an increase in caregiver life satisfaction, and vice versa. Caregiver background characteristics related to higher life satisfaction include being: married, a birth-parent, under 40 years old and having the absence of previous diagnoses of an emotional, behavioral or substance use disorder. CONCLUSION: Caregivers of clinically-referred youth report low levels of life satisfaction throughout youth treatment. Given the bi-directional influences on one another, tending to the well-being of caregivers may positively influence both caregivers and youths.